Utilizing Digital Technology for Character Development in Early Childhood Education: A Scoping Review - Jumiatmoko; Muthmainah; Aprinalistria (Indonesian Values and Character Education Journal, 2024)
Teachers and parents often lack examples of implementing digital technology in the development of character for early childhood. This study aims to analyze best practices in the application of digital technology for character development in young children. The method used is the Preferred Reporting Items for Systematic Review and Meta-Analyses extension for Scoping Review (PRISMA-ScR) to identify research reports on the use of digital technology for character development in early childhood over the past five years. The findings show that the applied digital technologies are divided into two types: audiovisual and visual. Through the perspective of Early Childhood Education for Sustainability (ECEfs), the use of digital technology has been proven effective in stimulating children's character, with the character composition of self-respect (31%), respect for others (38%), and respect for the environment (31%). Based on the 18 national character values according to Permendikbud No. 20 of 2018, only 33% of the character proportions are developed through digital technology. This study concludes that digital technology, both in audiovisual and visual forms, can be utilized by teachers and parents to support the development of character in early childhood. Socio-cultural and ecological systems theories are used to explain the role and potential of digital technology in character development for young children.